La princesa peleona - Waddell, Martin; Benson, Patrick; Ibeas, Juan Manuel (Madrid : Anaya, 1999)
A spunky princess with a mind of her own resists her parents' plans to ensnare a prince for her and rides forth to adventures of her own choosing.
"Facil de leer" -- Cover.
Translation of: The tough princess.
Keywords: Princesses -- Juvenile fiction; Fairy tales; Princesas -- Novela juvenil; Cuentos de hadas -- Literatura juvenil